Hubungan Persepsi Dan Kepatuhan Minum Obat Pada Lansia Penderita Diabetes Melitus Di Kelurahan Babakan Sari Berdasarkan Health Belief Model - Alfita, Aliyah Nur; Juniarti, Neti; Sari, Citra Windani Mambang (STIKES Suaka Insan, 2025)
Medication adherence is a key determinant for maintaining quality of life and preventing serious complications in older adults with diabetes mellitus. However, adherence is often hindered by various factors, particularly individual perceptions of the disease and its therapy. Negative perceptions or inadequate understanding can constitute a major obstacle to successful treatment outcomes. This study aimed to evaluate the association between the perceptions of older adults with diabetes, as measured by the Health Belief Model (HBM) framework, and their level of medication adherence. This cross-sectional, correlational study was conducted from November 20 to December 17, 2024, in the Babakan Sari sub-district. A sample of 64 respondents was recruited using simple random sampling. Data were collected using the Health Belief Model questionnaire and a medication adherence questionnaire, and subsequently analyzed using univariate and bivariate analysis with the Spearman Rank correlation test. The analysis revealed a statistically significant, strong positive relationship between HBM-based perceptions and medication adherence (r = .716, p < .001). Perceived barriers and perceived benefits were identified as the two most influential HBM components in determining medication adherence among older adults with diabetes mellitus. Interventions targeting these two perceptions have the potential to improve therapeutic success in this population.